Design aspects of cemented aggregate fill mixes for tungsten stoping operations - Arioglu, Ergin (Elsevier BV, 1984)
Abstract The use of cemented aggregates in fill practice has increased in recent years. Its effectiveness in fill design is widely accepted. In order to maximize its economy a rational approach to the mix design is essential. The purpose of the paper is to provide a basis for design of cemented aggregate fill mixes. The proposed method is based on data obtained from experimental investigations conducted for Uludaĝ Tungsten Mine in Turkey.